Control of penicillium expansum Link Causing Blue Mold of Pear Using Some Fungicides - Baviskar RN; Dekate HM (International Journal of Life Sciences, 2016)
Blue mold of pear is caused by Penicillium expansum Link. Thom. ex. is one of the most serious post harvest disease in India. Total twenty three isolates of P. expansum were isolated from infected pear fruits for sensitivity tested against carbendazim on Potato Dextrose Agar (PDA) medium. Sensitivity of these isolates to carbendazim was determined using food poisoning method. In vitro Minimum Inhibition Concentration (MIC) for carbendazim was determined; isolate Pe-9 MIC-750.6μg/ml was sensitive while isolate Pe-15 MIC-970.3 μg/ml was tolerant. In vivo Pe-9 MIC-1900.2μg/ml was sensitive. Pe-15 MIC-2470.3μg/ml was tolerant. Carbendazim resistant mutant (Pe-EMS-10, MIC-4850.6μg/ml) is equally important to manage using different fungicides. P. expansum was tested against carbendazim and other fungicides viz. dithane Z-78, polyram, acrobat, kocide, dithiocarbmate, thiobendazole and diphenylamine. In vitro results revealed that the Percentage Control Efficacy (PCE) values range at 50% Conc. (44.02 - 49.28%) while at 100% Conc. (50.89 - 61.39%) individually and in mixture with carbendazim increased its PCE from at 50% Conc. (55.39 - 68.98%) while at 100% (68.72 -73.57%). In vivo PCE at 50% Conc. (51.62 - 56.95%) individual and mixture (57.25 - 59.26%) while at 100% from alone (58.32 - 69.36%) and in mixture (71.63 - 79.82%) PCE further increased and without fungicide served as control.